Глуховский Петропавловский монастырь и его связи с Путивльской землёй - Чурочкин, А.А. (Сіверщина в історії України, 2020)
Статья посвящена связям Глуховского Петропавловского монастыря с Путивльской землей; на основании анализа новых открытий в сфере древнерусской княжеской генеалогии сделана попытка определить возможных основателей обители, атрибутирован
снимок одного из насельников обители начала ХХ века. Стаття присвячена зв'язкам Глухівського Петропавлівського монастиря з Путивльською землею; на підставі аналізу нових відкриттів у сфері давньоруської князівської генеалогії зроблена спроба визначити можливих засновників обителі, атрибутувати знімок одного з насельників обителі початку ХХ століття The article is devoted to the relations of the Glukhovsky Peter and Paul
Monastery with the Putivl land; based on the analysis of new discoveries
in the sphere of ancient Russian princely genealogy, an attempt was made
to identify the possible founders of the monastery, a photograph was
attributed to one of the inhabitants of the monastery at the beginning
of the 20th century.
Glukhovsky Peter and Paul Monastery is a true spiritual pearl of
the ancient Seversky land Unfortunately, the 20th century, cruel to
monuments of church antiquity, caused irreparable damage to its shrines
and architectural appearance. Until now, the monastery has not been used
for its original purpose, the lamp of monastic life does not warm in it.
It would seem that the Peter and Paul Monastery relates only to the
city of Glukhov, since it is called the “Glukhovsky”. Nevertheless, the
newly revealed data allow us to conclude that in the early stages of its
existence, the monastery of the Holy Apostles Peter and Paul had close
ties with the city of Putivl and its district.
The beginning of the history of the monastery, alas, is hidden from
us behind the veil of centuries. The continuous existence of the Peter and
Paul Monastery is reliably traceable only from the seventeenth century.
Nevertheless, almost all historical studies concerning this monastery,
referring to the traditions, stubbornly attribute its foundation back to pre-
Mongol time. There are references to 1230 to the second quarter of the 13th
century. In later documents sometimes absolutely fantastic information
also appears that one of the churches was allegedly built by “famous Greek
architects in 1112”. In a word, there is a steady tendency to attribute the
time of the founding of the monastery to the princely era. In this regard, I
would like to share my thoughts and assumptions on this subject.
The ancient cities of the Seversky land - Putivl and Glukhov, between
which, in fact, the Peter and Paul Monastery is located, during the period
of specific fragmentation were the centers of the principalities of the same
name. Each prince sought to leave a memory for future generations. Often,
such a memory became a temple or a monastery dedicated to the heavenly
patron saint of the prince. At one time, such a practice was quite common.
The present format of the article does not allow us to pay attention to
all the factors linking the Peter and Paul monastery with the Putivl land.
The first voiced version of the ancient Russian time of the founding of
the monastery, as well as an attempt to establish the name of a possible
founder, require additional study and clarification. It is absolutely necessary
to conduct a search and study of the monastery’s track records in order to
establish the worldly name, surname and origin of the monk Abel.
In the 20th century, we lost so much, and, even worse, we continue to
lose in the 21st century, so we need to cherish and painstakingly study the
little that has survived. I believe and hope that through the prayers of St.
Demetrius of Rostov, Archimandrite Melchizedek, the monk Abel and a host
of other nameless ascetics, the once glorious Peter and Paul Monastery
will regain its former glory and greatness.